Analysis of grayanatoxin in Rhododendron honey and effect on antioxidant parameters in rats - Sibel, Silici; Enis, Yonar M.; Huseyin, Sahin; Timucin, Atayoglu A.; Duran, Ozkok (Elsevier Ireland Ltd, 2014)
Ethnopharmacological relevance: Rhododendron honey, locally known as mad honey, contains gryanotoksin (GTX) and thus induces toxic effects when consumed in large amounts. But, it is still popularly used for treating medical conditions such as high blood pressure or gastro-intestinal disorders. The aim of this study was to evaluate the effect of GTX on antioxidant parameters measured from rats fed with Rhododendron honey. Material and methods: A total of sixty Sprague-Dawley female rats were divided into five groups of 12 rats each, one being the control group (Group 1) and the others being the experimental groups (Groups 2 to 5). Group 2 was treated with 0.015 mg/kg/bw of Grayanotoxin-III (GTX-III) standard preparation via intraperitoneal injection. Groups 3, 4 and 5 were respectively given Rhododendron honey (RH) at doses of 0.1, 0.5, and 2.5 g/kg/bw via oral gavage. After one hour, blood samples were collected from the rats. Glutathione peroxidase (GSh-Px), superoxide dismutase (SOD), catalase (CAT) activities and malondialdehyde (MDA) contents were examined in blood, heart, lungs, liver, kidney, testicles, epididiymis, spleen and brain specimens. Results: The data from the rats in Groups 2 (GTX) and 5 (RH at 2.5 g/kg/bw) showed negative effect on the antioxidants parameters in blood and all tissue samples examined at the specified doses and time period. Administration of GTX to rats at dose of 0.015 mg/kg/bw resulted in lipid peroxidation. (This part needs to be enhanced more). Conclusion: It has been observed that both Grayanotoxin and high dose Rhododendron honey treatments showed oxidant effect on blood plasma and organ tissues investigated. (C) 2014 Elsevier Ireland Ltd. All rights reserved.
Keywords: Rhododendron (mad) Honey; Grayanotoxin; Antioxidant activity; MDA; Rat